2014
DOI: 10.3109/02699052.2014.979229
|View full text |Cite
|
Sign up to set email alerts
|

Objective assessment of visual attention in mild traumatic brain injury (mTBI) using visual-evoked potentials (VEP)

Abstract: The objective and subjective tests were able to differentiate between those having mTBI with and without an attentional deficit. The proposed VEP protocol can be used in the clinic to detect and assess objectively and reliably a visual attentional deficit in the mTBI population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…Possible magnocellular deficits have been reported for individuals with a history of mild traumatic brain injury compared with visually normal control subjects based on their P100 visually evoked potential responses to a high-contrast (85%) checkerboard stimulus (1.49-cycle/degree check size) at a very low luminance level (0.3% transmittance; greater P100 latency and smaller amplitude),15 as well as to low-contrast (20%) checkerboard stimuli of varying sizes (smaller P100 amplitude) 16. Observation of magnocellular deficits in mild traumatic brain injury is also consistent with the results of several non–visually evoked potential studies, which found an elevated coherent motion threshold,17 increased visual motion sensitivity,18 and elevated and increased critical flicker frequency threshold values 19,20…”
mentioning
confidence: 99%
“…Possible magnocellular deficits have been reported for individuals with a history of mild traumatic brain injury compared with visually normal control subjects based on their P100 visually evoked potential responses to a high-contrast (85%) checkerboard stimulus (1.49-cycle/degree check size) at a very low luminance level (0.3% transmittance; greater P100 latency and smaller amplitude),15 as well as to low-contrast (20%) checkerboard stimuli of varying sizes (smaller P100 amplitude) 16. Observation of magnocellular deficits in mild traumatic brain injury is also consistent with the results of several non–visually evoked potential studies, which found an elevated coherent motion threshold,17 increased visual motion sensitivity,18 and elevated and increased critical flicker frequency threshold values 19,20…”
mentioning
confidence: 99%
“…This system has been approved by the FDA, and it has been used in our laboratory for the last 4 years for a variety of VEP studies. [26][27][28]35,37 The Diopsys company developed a custom-designed software program to measure quantitatively the alpha power responses via power spectrum analysis (Dumermuth and Molinari, 1987). 32 The power spectrum analysis filters and extracts the power (unit = µV2) of each alpha single frequency (i.e., 8, 9, 10, 11, 12, and 13 Hz) that is embedded in the overall complex VEP response waveform using Fourier analysis 38 (Figure 3).…”
Section: Apparatusmentioning
confidence: 99%
“…The OVR consisted of training each of the three oculomotor systems, i.e., version, vergence, and accommodation, with such training indirectly including an attentional component. 34, 35 OVR was performed twice a week for six weeks for a total of 9 hours, 3 hours for each oculomotor system. There was also a similar placebo arm to the protocol (see Thiagarajan [43][44][45][46][47][48] for details).…”
Section: Oculomotor Vision Rehabilitation (Ovr) and The Vepmentioning
confidence: 99%
See 2 more Smart Citations